Analisis Tarif Berdasarkan Biaya Operasional Kendaraan Pada Travel Jurusan Palangka Raya - Muara Teweh - Friskila, Friskila; Elvina, Ina; Murniati, Murniati (Jurnal Basement : Jurnal Teknik Sipil, 2025)
The economy of a region or country is highly dependent on transportation, which also serves a number of different human needs, including those related to the economy, education, health, and other fields. Using the 2002 Directorate General of Land Transportation technique, this study attempts to determine the Motor Vehicle Operating Cost on the Palangka Raya City - Muara Teweh route. Interview surveys are used as a research technique to collect information on the Vehicle Operating Cost from motor vehicle transportation service providers, especially CV. Putra Borneo Travel, which offers the Palangka Raya City - Muara Teweh route. In accordance with the established tariff law, the motor vehicle operating cost on the Palangka Raya City - Muara Teweh route is analyzed to determine the financial feasibility of the base rate for service providers. According to the analysis findings, the motor vehicle operating cost on the Palangka Raya City - Muara Teweh route owned by CV. Putra Borneo Travel is IDR 2,574.10 per vehicle-kilometer. For service providers such as CV. Putra Borneo Travel, the basic passenger fare is IDR 188,382/pnp, which is financially feasible. This CV, which offers travel transportation services, charges IDR 250,000 per person